Sensing danger in the islet: the roles of pattern recognition receptors in β cells and type 1 diabetes - Tong, Lixiang; Tu, Yiting; Huang, Shoujun; Zheng, Peilin (Frontiers in Immunology, 2025)
Type 1 diabetes (T1D) is an organ-specific autoimmune disease characterized by the immune-mediated destruction of pancreatic β cells, leading to absolute insulin deficiency and chronic hyperglycemia. Traditionally, the onset of T1D has been attributed to the interplay of genetic predisposition and environmental factors that disrupt immune tolerance. However, growing evidence suggests that β cells are not merely passive targets of immune attack. Instead, under conditions of inflammatory and metabolic stress, β cells actively participate in immune modulation by upregulating various immunologically relevant molecules, particularly pattern recognition receptors (PRRs). These innate immune sensors enable β cells to detect danger-associated signals and modulate local immune responses, thereby influencing their survival and immunogenicity. In this review, we summarize current knowledge about the expression profiles and immunoregulatory roles of PRRs in pancreatic β cells and explore their potential contributions to T1D pathogenesis. A deeper understanding of PRR-mediated signaling in β cells may provide novel insights into the immunopathology of T1D and reveal promising targets for therapeutic intervention.